Changes of aroma components of 'Petit Verdot' grape berries and wines from Hebei Jieshi Mountain region during fermentation process - LIU Siyu, WU Yangpeng, SHI Tonghua, CUI Yanzhi, LAN Yibin, DUAN Changqing, PAN Qiuhong (Zhongguo niangzao)
The changes of composition and contents of aroma compounds in the berries and wines during fermentation process of 'Petit Verdot' grapes from the Jieshi Mountain region in Hebei, China was analyzed by headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS), odor active value (OAV) and sensory quantitative descriptive analysis (QDA). The results demonstrated that 18 components of C13-norisoprenoids and terpenoids were identified in grape berries. Among them, the OAV of β-damascenone in wine was up to 50. The C6 compounds synthesized by the lipoxygenase metabolism pathway were the most predominant components in the berries. In the wine, only the OAV of 1-hexanol and hexanoic acid exceeded 1. Phenylethanol and phenylacetaldehyde produced by the amino acid metabolism also had high OAV in wines, which contributed to the rosy and sweet aroma. Esters were produced primarily during the alcohol fermentation stage, of which 12 esters with OAV>1, imparting strong fruity, floral and sweet aromas. However, ethyl lactate and isoamyl lactate decreased during the malolactic fermentation stage, while most esters increased, resulting in a notable alteration of the aroma profile. The analysis of OAVs and sensory evaluation indicated that ethyl lactate, ethyl caprylate, β-damascenone, and isoamyl acetate were potential important compounds determining the aroma profile of 'Petit Verdot' wines. These findings provided a basis for controlling the aroma quality in the production of 'Petit Verdot' wine.